Co-pyrolysis of lignite and sugar beet pulp - Yilgin, M.; Duranay, N. Deveci; Pehlivan, D. (Pergamon-Elsevier Science Ltd, 2010)
Today, worldwide studies have been undertaken on the biomass usage and co-conversion of biomass and coal to seek out alternative fuels for supplying energy in an environmental friendly way. The objective of this work is to study co-pyrolysis of lignite and sugar beet pulp in 50/50 (wt./wt.) ratio of blend pellets, to elucidate their thermal behaviour under pyrolysis conditions and to assess major decomposition products in terms of their yields. A special chamber, which has enabled very fast heating rates, was used in the pyrolysis experiments carried at 600 degrees C. The results were interpreted in the light of liquid, solid and gaseous yields, resulting from thermal decomposition, and kinetics of thermogravimetric analysis. Proximate volatile matter and ash contents of the blends were different compared to those found by using individual values. Sugar beet pulp decomposed faster within a relatively narrow temperature range than lignite and underwent a significant shrinkage during pyrolysis. It was found that the chars left behind after the flash pyrolysis of these pellets at 600 degrees C have substantial amounts of volatile matter that would evolve upon further heating. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Lignite; Sugar beet pulp; Co-pyrolysis; Pellet; TGA